Expanded use of aggressive therapies improves survival in early and intermediate hepatocellular carcinoma. Issue 8 (28th January 2014) - Ho, Edith Y.; Cozen, Myrna L.; Shen, Hui; Lerrigo, Robert; Trimble, Erica; Ryan, James C.; Corvera, Carlos U.; Monto, Alexander; HOVAS Group (Hepatocellular Carcinoma Treatment Outcome at VA San Francisco)
Abstract Background Despite the increasing annual incidence of hepatocellular carcinoma (HCC) in the USA, now estimated at 2.7 cases per 100 000 population, only a small proportion of patients receive treatment and 5‐year survival rates range from 9% to 17%. Objectives The present study examines the effects of multimodal treatment on survival in a mixed‐stage HCC cohort, focusing on the impact of radical therapy in patients with Barcelona Clinic Liver Cancer (BCLC) stage B disease. Methods A retrospective review of the medical records of 254 patients considered for HCC treatment between 2003 and 2011 at a large tertiary referral centre was conducted. Results A total of 195 (76.8%) patients were treated with a median of two liver‐directed interventions. Median survival time was 16 months. In proportional hazards analysis, radiofrequency ablation (RFA) and resection were associated with significantly improved 1‐ and 5‐year survival among patients with BCLC stage 0–A disease. In patients with BCLC stage B disease, RFA conferred a survival benefit at 1 year and resection was associated with significantly improved survival at 5 years. Conclusions As one of few studies to track the complete course of sequential HCC therapies, the findings of the present study suggest that HCC patients with intermediate‐stage (BCLC stage B) disease may benefit from aggressive interventions not currently included in societal guidelines.